Analisis Mutu Organoleptik Sirup Kayu Manis Dengan Modifikasi Perbandingan Konsentrasi Gula Aren Dan Gula Pasir - Dewi Arziyah; Lisa Yusmita; Ruri Wijayanti (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2022)
Cinnamon has the potential to be developed into a drink in the form of syrup by modifying the concentration ratio of palm sugar and granulated sugar. Food assessment methods that use the five senses are organoleptic assessments and are generally called sensory tests. Assessment with these senses, is widely used to assess the quality of agricultural commodity products. The organoleptic test was carried out by 20 untrained panelists. The results showed that the comparison of the concentration of granulated sugar and palm sugar that the panelists preferred the most was in treatment C, namely the concentration of 50% palm sugar and 50% granulated sugar. The value of color preference is 3.7, taste is 3.6 and aroma is 3.5. The comparison of the concentration of palm sugar and granulated sugar which the panelists did not like was in treatment B, with a ratio of 25% palm sugar and 75%